1999
DOI: 10.1002/(sici)1097-0231(19991230)13:24<2489::aid-rcm816>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Observation of daunomycin and nogalamycin complexes with duplex DNA using electrospray ionisation mass spectrometry

Abstract: The noncovalent binding of the antitumour drugs daunomycin and nogalamycin to duplex DNA has been studied using electrospray ionisation mass spectrometry (ESI-MS). The conditions for the preparation of drug/duplex DNA complexes and for their detection by ESI-MS have been optimised. Ions corresponding to these complexes were most abundant relative to free DNA when prepared in the pH range 8-9, and using gentle ESI interface conditions. Self-complementary oligonucleotides, 5'-d(GGCTAGCC)-3' or 5'-d(CGGCGCCG)-3',… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…The lack of a well-defined DNA binding stoichiometry by the antibiotic analogs is reminiscent of results reported by Gabelica et al for drug-DNA complexes containing known intercalators such as ethidium bromide, amsacrine, and ascididemin [16]; as well as Kapur et al for the more complex intercalators daunomycin and nogalamycin [36]. In the study by Gabelica, the DNA-binding modes observed in the gas-phase for ethidium bromide, amsacrine, and ascididemin exhibited the non-specific multiple-drug binding which parallels the binding behaviors observed in solution [16].…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 78%
See 1 more Smart Citation
“…The lack of a well-defined DNA binding stoichiometry by the antibiotic analogs is reminiscent of results reported by Gabelica et al for drug-DNA complexes containing known intercalators such as ethidium bromide, amsacrine, and ascididemin [16]; as well as Kapur et al for the more complex intercalators daunomycin and nogalamycin [36]. In the study by Gabelica, the DNA-binding modes observed in the gas-phase for ethidium bromide, amsacrine, and ascididemin exhibited the non-specific multiple-drug binding which parallels the binding behaviors observed in solution [16].…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 78%
“…However, the relative peak intensities also paralleled ligand polarity, including ligand charge, and thus the observed binding pattern could simply be an artifact of the electrospray process. The peak distribution patterns reported by Kapur et al for daunomycin and nogalamycin were interpreted as following the neighbor exclusion principle predicted for intercalators, in which one drug molecule is inserted between every other base pair in the duplex DNA [36].…”
Section: Complexation Of Dna and Uk-1 Analogs Without Metalsmentioning
confidence: 79%
“…Mixtures of dsDNA with [Ru(phen) 2 dpq]Cl 2 or [Ru(phen) 2 dpqC]Cl 2 were prepared as previously described [15]. It should be noted that in our laboratory we have established that no significant differences in the relative abundances of drug-dsDNA complexes are observed when the drugs are added either after or during annealing of the DNA with the non self-complementary 16 mers used in these experiments [6,14].…”
Section: Preparation Of Dsdna-drug Complexesmentioning
confidence: 99%
“…Electrospray ionization mass spec-trometry (ESI-MS) has substantial potential for this purpose. Several research groups have used ESI-MS to assess the relative affinities and stoichiometries of drugs that bind to DNA [5,6]. Although many noncovalent complexes have been studied by ESI-MS, questions remain as to the extent to which complexes detected in the gas phase reflect the solution equilibrium position existing prior to injection into the mass spectrometer [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation